Immediate weight loss before ovarian stimulation with intrauterine insemination is associated with a lower risk of preeclampsia in women with obesity and unexplained infertility - Robert A. Wild, M.D., M.P.H., Ph.D; Rodney K. Edwards, M.D; Daniel Zhao, Ph.D; Ashley S. Kim, M.D; Karl R. Hansen, M.D., Ph.D (Elsevier, 2022)
Objective: To determine whether successful weight loss before ovarian stimulation with intrauterine insemination (OS-IUI) affects the risk of future pregnancy complications among women with obesity and unexplained infertility after fertility treatment. Design: Secondary analysis of the randomized controlled clinical trial Improving Reproductive Fitness Through Pretreatment With Lifestyle Modification in Obese Women With Unexplained Infertility (FIT-PLESE). Setting: Multiple academic health centers in the United States. Patient(s): Three hundred seventy-nine women with obesity and unexplained infertility who underwent standard infertility treatment after a lifestyle intervention. Intervention(s): The FIT-PLESE trial evaluated whether prepregnancy lifestyle interventions (diet with weight loss medication and exercise vs. exercise alone) before OS-IUI improved the live birth rate among women with obesity and unexplained infertility. Although the primary outcome of FIT-PLESE was live birth rate, we compared the demographics and subsequent pregnancy complications of women who successfully lost some weight with those of women who did not lose any during the interventions. Main Outcome Measure(s): Obstetric complications by groups were compared using χ2 and Fisher's exact tests, and continuous variables were compared using Student's t-tests. Logistic regression was used to assess the odds of preeclampsia after adjustment for the randomized treatment arm in FIT-PLESE. Result(s): There was a nonsignificant trend toward a lower risk of intrauterine growth restriction (4% vs. 16%, P = .124) and preterm delivery (6% vs. 15%, P = .343) among patients who lost at least some weight. The risk of preeclampsia was significantly lower (6% vs.35%, P = .002) in the weight loss group (odds ratio, 0.09; 95% confidence interval, 0.016-0.505; P = .006) after adjustment for treatment assignment. Conclusion(s): Among women with obesity and unexplained infertility who had live births after fertility treatment, prepregnancy weight loss due to lifestyle interventions before OS-IUI was associated with a lower risk of preeclampsia.